2015
DOI: 10.3389/fpsyg.2015.00062
|View full text |Cite
|
Sign up to set email alerts
|

Allocentric spatial learning and memory deficits in Down syndrome

Abstract: Studies have shown that persons with Down syndrome (DS) exhibit relatively poor language capacities, and impaired verbal and visuoperceptual memory, whereas their visuospatial memory capacities appear comparatively spared. Individuals with DS recall better where an object was previously seen than what object was previously seen. However, most of the evidence concerning preserved visuospatial memory comes from tabletop or computerized experiments which are biased toward testing egocentric (viewpoint-dependent) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
57
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 91 publications
6
57
1
Order By: Relevance
“…It is difficult to identify the HSA21 genes with their triple copy being associated with ID because of the small number of segmental trisomies (Higurashi et al 1990 ;Poissonnier et al 1976 ). Another difficulty is the heterogeneity of the cognitive profile as some cognitive processes are strongly impacted while others are less impaired (Chapman and Hesketh 2001 ;Lavenex et al 2015 ;Patterson et al 2013 ;Vicari and Carlesimo 2006 ). This heterogeneity and the lack of validity of certain cognitive measures can explain discrepancies between studies (Delabar et al 1993 ;Korenberg et al 1994 ;Lyle et al 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult to identify the HSA21 genes with their triple copy being associated with ID because of the small number of segmental trisomies (Higurashi et al 1990 ;Poissonnier et al 1976 ). Another difficulty is the heterogeneity of the cognitive profile as some cognitive processes are strongly impacted while others are less impaired (Chapman and Hesketh 2001 ;Lavenex et al 2015 ;Patterson et al 2013 ;Vicari and Carlesimo 2006 ). This heterogeneity and the lack of validity of certain cognitive measures can explain discrepancies between studies (Delabar et al 1993 ;Korenberg et al 1994 ;Lyle et al 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Courbois et al (2013) reported that, although individuals with DS could learn specific spatial routes in a virtual environment, albeit more slowly than MA-matched controls, they were unable to find a novel shortcut between two learned locations, suggesting difficulty with using spatial memory flexibly. Extending on this research using a real-world, spatial memory task, Banta Lavenex et al (2015) showed that individuals with DS learned and remembered associations between an object and its location similarly to MAmatched controls, but only when the location of the hidden object was cued by a colour. That is, memory was not impaired when participants could use a visual landmark to facilitate their memory for the hidden object.…”
mentioning
confidence: 85%
“…(), this condition requires participants to form a flexible spatial representation of the area (Banta Lavenex et al . ). Both of these studies suggest that people with DS demonstrate particular impairments in linking individual details of an event into a flexible, relational framework.…”
mentioning
confidence: 97%
See 2 more Smart Citations